Analisis Indikator Yang Mempengaruhi Auditor Dalam Memberikan Opini Going Concern Pada Suatu Perusahaan Dengan Pendekatan Isa 570 (Perusahaan Yang Terdaftar Di Bei Periode 2014) - Trenggono, Lintang; Alit Triani, Ni Nyoman (AKRUAL: JURNAL AKUNTANSI, 2015)
AbstractThis study aimed to analyze the indicators that affect the auditor in providing a going concern audit opinion to the companies that listed on the Indonesian Stock Exchange in 2014. The variables in this study is the financial condition of the company, the companys growth, debt default, the current ratio, RoA, audit opinion in previous year, the companies compliance with laws and regulations. The sample in this study are all companies listed on the Indonesian Stock Exchange (BEI) in 2014 using saturation sampling technique and acquired 485 companies that meet the criteria of representatif sample. The results ofresearch conducted by using the test model regression logistic indicates that the variable debt default and the audit opinion in previous year have an affects to the providing of going concern audit opinion and variable financial condition of the company, the companys growth, the current ratio, RoA, companies compliance with laws and regulations have no effect tothe providing of going concern audit opinion.